Decision Making Status regarding Antenatal Care among Women in a Tertiary Level Hospital, Kathmandu - Mainali, Srijana; Pandey Bista, Archana (Journal of Institute of Medicine Nepal, 2024)
Introduction Women’s decision making is one of the important indicators of maternal health which directly influence their utilization of antenatal care services resulting on reduction maternal morbidity and mortality. The aim of this study was to find out the decision making status regarding antenatal care among women. Methods A cross-sectional study was conducted among 180 antenatal women of third trimester from Gynae/Obs OPD of Tribhuvan University Teaching Hospital. Non-probability purposive sampling technique was adopted. Data was collected by using semi-structure interview questionnaire. Data were analyzed using descriptive statistic and inferential statistics using chi square and fisher’s exact test. Results Findings of this study clearly explain medium level of decision making in large number of respondents. More than two-thirds research participant (123, 68.3%) had medium level of decision making on antenatal care, whereas few respondents (30, 16.7%) had high level of decision making. The study revealed that there was statistical association of level of decision making with women’s age (p=0.009), type of family (p=0.01), duration of marriage (p=0.002), economic status (p=0.009), education (p=0.007) and number of children (< p=0.001). Conclusion Few of the antenatal women have high level of decision-making status regarding their antenatal care. Furthermore, the lowest level of decision making was observed concerning on autonomy in financial matter. Thus the importance of advocacy for promoting women’s decision-making status in our context is necessary.